2006
DOI: 10.1007/s00281-006-0056-x
|View full text |Cite
|
Sign up to set email alerts
|

FcγRII and multi-system autoimmune disease

Abstract: The FcR are a crucial link in the immune response between humoral and cellular immunity and cell-based effector systems, mediating a wide variety of physiological and biochemical responses. The FcR for IgG (FcgammaR) and in particular the most widely expressed of these, FcgammaRII, are important in regulating adaptive immunity. Disruption of their function is a key factor in the development of autoimmune diseases such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA), which are characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…25 As such, the IC deposits may induce an acute inflammatory reaction, clinically translated as inflammatory pain in muscles and joints. 4 Allelic variance of FcgRIIa with a single nucleotide polymorphism (SNP) changing amino acid 131, determines the binding affinity for IgG1. 26,27 Arginine (R) at 131 results in an increased ability to bind IgG1, while histidine (H) at 131 reduces binding of IgG1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 As such, the IC deposits may induce an acute inflammatory reaction, clinically translated as inflammatory pain in muscles and joints. 4 Allelic variance of FcgRIIa with a single nucleotide polymorphism (SNP) changing amino acid 131, determines the binding affinity for IgG1. 26,27 Arginine (R) at 131 results in an increased ability to bind IgG1, while histidine (H) at 131 reduces binding of IgG1.…”
Section: Discussionmentioning
confidence: 99%
“…In this capacity, increased expression of activating FcR, including FcgRIIa, on monocytes and macrophages has been associated with a subsequent increase in production of inflammatory cytokines. 4 While the acute manifestations of dengue are well known, 5 only a limited number of studies have reported the unique clinical manifestations occurring during the early convalescent phase of infection, which may have an autoimmune component in their development. [6][7][8][9] Further, the longterm consequences of the cross-reactivity of dengue antibodies and their effect on plasmin activity, 10 which may increase the long-term risks of hemorrhage among infected patients, also remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fcgamma receptors (FcgRs) provide crucial links between humoral and cellular immune responses, and as such are important in immune homeostasis and response to pathogens. 1 FcgR interactions with immune complexes can, however, lead to cellular activation, triggering an inflammatory cascade and tissue destruction. 2 Five subclasses of FcgR are known in humans, including four activating receptors (FcgRI, FcgRIIa, FcgRIIIa and FcgIIIb), and one inhibitory receptor (FcgRIIb).…”
mentioning
confidence: 99%
“…Non-neutralizing antibodies circulating in the serum of the patients enhance viral entry through the Fc receptor and worsen the course of infection [49]. An increased expression of Fc activating receptors on the monocytes and macrophages is associated with an increase in the production of inflammatory cytokines [50]. The following autoimmune markers were assessed in a subset of asymptomatic individuals: complement factors C3/C4, rheumatoid factor (RF), C-reactive protein (CRP), antinuclear antibodies (ANA), and immune complexes (IC).…”
Section: Long-term Sequelae Of Denguementioning
confidence: 99%